RECORD OF HOST PLANTS AND NATURAL ENEMIES OF TURAL ENEMIES OF SOLENOPSIS MEALYBUG, PHENACOCCUS SOLENOPSIS COCCUS SOLENOPSIS COCCUS SOLENOPSIS TINSLEY: A POTENTIAL PEST UNDER PROTECTED CULTIVATION IN HIMACHAL PRADESH - SINGH, VINAY; SOOD, A. K; MEHTA, P. K (The Bioscan, 2016)
Survey studies conducted in low hill regions of Himachal Pradesh to record the incidence and source of infestation of solenopsis mealybug Phenacoccus solenopsis Tinsley in the protected structures revealed 12 plant species belonging to 8 families comprising vegetables, ornamentals, weed and fruit and forest plants as the hosts to P. solenopsis. The incidence categorized in grade I-IV based on the severity of infestation revealed six plant species namely, Capsicum annuum Linn., Lantana camara Linn., Lycopersicon esculentum Mill., Malvastrum coromandelianum (L.) Garcke, Malvaviscus penduliflorus DC. and Parthenium hysterophorus Linn. to be the preferred host. The others, Abelmoschus esculentus Linn., Achyranthes aspera Linn., Bombax ceiba Linn., Codiaeum variegatum (L.) A. Juss., Jatropha curcas Linn. and Mangifera indica Linn. were grouped in grade I-III with low to moderate incidence. Majority of the host plants recorded (66.7%) were situated on field peripheries, road sides and village paths and served as sources of infestation of solenopsis mealybug. Five coccinellid predators (Harmonia dimidiata (Fabricius), Chilocorus nigrita (Fabricius), Coccinella septempunctata Linn., Harmonia dimidiata (Fabricius) and Oenopia sauzeti Mulsant) and one hymenopteran parasitoid (Aenasius arizonensis (Girault) (syn. A. bambawalei Hayat)) were found associated with P. solenopsis. All these constituted new record of the host plants and natural enemies of P. solenopsis from Himachal Pradesh.